Prostacyclin for pulmonary hypertension in adults - Paramothayan, N Shanthi (Cochrane Database Syst Rev, 2005)
BACKGROUND: Primary pulmonary hypertension (PPH) is progressive, resulting in right ventricular failure. Pulmonary hypertension can be idiopathic or associated with other conditions. Prostacyclin is a potent vasodilator and inhibitor of platelet aggregation, and can be given orally, subcutaneously, intravenously or inhaled via a nebuliser. OBJECTIVES: To determine the efficacy of prostacyclin or one of its analogues in idiopathic primary pulmonary hypertension. SEARCH METHODS: Electronic searches were carried out in CENTRAL, MEDLINE and EMABSE with pre‐specified terms. Searches were current as of July 2006. SELECTION CRITERIA: Two reviewers selected randomised controlled trials (RCTs) involving adults with pulmonary hypertension for inclusion. DATA COLLECTION AND ANALYSIS: Study quality was assessed and data extracted independently by two reviewers. Outcomes were analysed as continuous and dichotomous outcomes. We sub‐grouped data where possible by aetiology of PH (PPH, PH secondary to connective tissue disorder or mixed populations). MAIN RESULTS: Nine RCTs of mixed duration (3 days‐52 weeks), recruiting 1175 participants were included (NYHA functional classes II‐IV). Intravenous prostacyclin versus usual care (four studies): There were significant improvements in exercise capacity of around 90 metres, cardiopulmonary haemodynamics and NYHA functional class over 3 days‐12 weeks. Effects were consistent in primary and secondary pulmonary hypertension. Oral prostacyclin versus placebo (two studies): Short‐term data (3‐6 months) indicated that there was a significant improvement in exercise capacity, but data from one study of 52 weeks reported no significant difference at 12 months. No significant differences were observed for any other outcome. Subcutaneous treprostinil versus placebo (two studies, 8‐12 weeks): One large study reported a significant median improvement in exercise capacity of around 16 metres. Cardiopulmonary haemodynamics and symptom scores favoured treprostinil. Infusion site pain and withdrawals due to adverse events were more frequent with treprostinil. Inhaled prostacyclin versus placebo (one study, 12 weeks): There was a significant increase in exercise capacity of approximately 36 metres. Treatment led to better symptom scores and functional class status than with placebo. Subgroup analyses reported by individual studies showed a better exercise capacity in participants with PPH, than those participants with PH secondary to other diseases. Side effects and adverse events were common in the studies. AUTHORS' CONCLUSIONS: There is evidence that intravenous prostacyclin in addition to conventional therapy at tolerable doses optimised by titration, can confer some short‐term benefits (up to 12 weeks of treatment) in exercise capacity, NYHA functional class and cardiopulmonary haemodynamics. There is also some evidence that patients with more severe disease based upon NYHA functional class showed a greater response to treatment.